Adaptation of Tajikistan International Students to Indonesian Culture - Turistiati, Ade Tuti; Narmadi, Hanugrah Banyu; Monk, Lincoln James Faikar (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
The culture of Tajikistan and Indonesia is very different. Some of the differences found include differences in language, traditions, and customs, types of food and how to cook it, and so on This study explored the phenomenological details of Tajik students who study in Purwokerto. The specifics revolved around the adaptation strategy to the Indonesian culture. A qualitative research method with a phenomenological study approach is used in this study. Data was gathered through in-depth interviews, observation, and review of relevant previous research articles and documents. According to the study's findings, the similarity of religious background (Islam) is a medium that allows Tajik students to bridge and make friends with residents or Indonesians. Language skills are essential in intercultural communication with local citizens (classmates, lecturers, and society). Learning national and local languages (Indonesian and Javanese) and English is extremely beneficial in intercultural communication. Tajik students are more likely to engage in low-contact communication, patriarchal systems, collectivism, and value feminism. Food and climate differences can cause culture shock.